Precise Near-Infrared Radial Velocities. Issue Volume 10:Issue S314(2015) (November 2015) - Plavchan, Peter; Gao, Peter; Gagne, Jonathan; Furlan, Elise; Brinkworth, Carolyn; Bottom, Michael; Tanner, Angelle; Anglada-Escude, Guillem; White, Russel; Davison, Cassy; Mills, Sean; Beichman, Chas; et al.
Abstract: We present the results of two 2.3 μm near-infrared (NIR) radial velocity (RV) surveys to detect exoplanets around 36 nearby and young M dwarfs. We use the CSHELL spectrograph ( R ~ 46, 000) at the NASA InfraRed Telescope Facility (IRTF), combined with an isotopic methane absorption gas cell for common optical path relative wavelength calibration. We have developed a sophisticated RV forward modeling code that accounts for fringing and other instrumental artifacts present in the spectra. With a spectral grasp of only 5 nm, we are able to reach long-term radial velocity dispersions of ~20–30 m s −1 on our survey targets.